Pembelajaran Keterampilan Membaca Kritis Berbasis Pendekatan Kontekstual pada Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia: Critical Reading Skills Learning Based on a Contextual Approach for Students of the Indonesian Language and Literature Education Study Program - Seni, Maria Kristiani; Salam, Salam; Nurhusna, Nurhusna (Journal Studies in Indonesian Language and Literature, 2025)
This research is a qualitative study aims to (1) identify the obstacles experienced by students on learning critical reading skills based on contextual approaches. (2) Assessing student perceptions of learning critical reading skills based on contextual approaches. The data in this study are descriptive data related to students' perceptions and obstacles in learning critical reading skills based on a contextual approach. The data sources for this study were class D students of the Indonesian Language and Literature Education Study Program, Makassar State University, intake 2021. Data collection techniques used included questionnaires and document analysis. The results of this study showed, (1) student barriers to adclose excess information, complex technical terms, lack of references and examples, long texts, as well as internal and external disorders that affect concentration. (2) Student perception involves understanding, analysis, evaluation of information in depth, and the application of theory in a real context to improve the ability to think critically. Students face various obstacles in learning critical reading skills based on contextual approaches, but they still have a positive perception because the learning encourages understanding, analysis, evaluation, and application of theory in a real context to develop critical thinking skills.